Hubungan Tingkat Kecemasan dengan Motivasi Kerja Perawat di RSUD dr. Soeratno Gemolong - Dinar Ariasti; Artha Tri Handayani (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2019)
Background: Anxiety is something that is naturally experienced by every human being. Not a few people who experience anxiety when carrying out their work. High workloads, a risky work environment and high professional demands create a lot of pressure faced by individuals while working. Based on the results of interviews with three nurses in the internal medicine room, many expressed their enthusiasm for working to decline. This happens because of concerns about contracting diseases experienced while working and benefits that have not been fulfilled. The purpose: This study was to determine the relationship between anxiety level and work motivation of nurses in the Internal Medicine Room of the RSUD Dr. Soeratno Gemolong. The subjects The population in this study were nurses who served in the internal medicine room of the RSUD dr. Soeratno Gemolong Sragen is in Teratai and Tulip room, which consists of 32 nurses. Methods: This research use correlation research design with a cross sectional method approach. The data collection tool used is a questionnaire to measure the level of anxiety and work motivation of nurses at Dr. Soeratno Gemolong Sragen. The results of the study: there were 26 respondents (81.25%) had mild anxiety levels, 5 respondents (15.62%) had moderate anxiety levels and 1 respondent (3.13%) had severe anxiety levels. Found 18 people (56.25%) had moderate work motivation, 11 people (34.38%) had high work motivation and 3 respondents (9.37%) had low work motivation. The results of the test using Rank Spearman SPSS version 18.0 program with Î± = 1% (0.01) obtained the number of correlation coefficients (r) = 0.552 which means that the level of correlation is strong between variables of anxiety level with work motivation. The results of the significance values for this study were 0.001 (Î± <0.05) which can be interpreted as having a significant relationship between the level of anxiety and work motivation. The conclusion of this study: there is a a relationship between the level of anxiety and work motivation in Dr. Soeratno Gemolong Hospital Sragen. Keywords: level of anxiety, work motivation